2021
DOI: 10.1002/hed.26846
|View full text |Cite
|
Sign up to set email alerts
|

Transoral endoscopic thyroidectomy vestibular approach: Experience from a multicenter national group with 412 patients

Abstract: Background: Well-established conventional thyroidectomy has satisfactory outcomes; however, robotic and endoscopic thyroid surgery can avoid visible anterior neck scars. Transoral endoscopic thyroidectomy vestibular approach (TOETVA) is the most recent of these techniques. Methods: This was a retrospective review of 412 patients who underwent TOETVA from 2017 to 2020 in 13 Brazilian centers. Results: The study included 359 (87.1%) females and 53 (12.9%) males, with a mean age of 40 years. There were 231 (56.1%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 32 publications
6
20
0
5
Order By: Relevance
“…The safety and feasibility of TOETVA have also been confirmed in different centers [ 31 33 ]. Compared with previous studies, the rate of permanent RLN injury in this study is lower [ 18 , 20 , 34 , 35 ], which may benefit from the neuroprotective techniques mentioned above.…”
Section: Discussionmentioning
confidence: 93%
“…The safety and feasibility of TOETVA have also been confirmed in different centers [ 31 33 ]. Compared with previous studies, the rate of permanent RLN injury in this study is lower [ 18 , 20 , 34 , 35 ], which may benefit from the neuroprotective techniques mentioned above.…”
Section: Discussionmentioning
confidence: 93%
“…In a study of TET using the TOVA, Anuwong et al reported a 10.9% incidence. 6 In another TOVA study, Lira et al reported transient and persistent hypocalcemia rates of 4.0% and 0.8%, respectively; 3 yet another noted a 14.1% incidence of transient hypoparathyroidism. 10 A meta-analysis of endoscopic and open thyroidectomy in PTC patients showed that rates of transient hypocalcemia after endoscopic resection ranged between 0.3% and 49%; those for permanent hypocalcemia ranged from 0% to 13%.…”
Section: Discussionmentioning
confidence: 96%
“… 2 The incidence of complications, including hypoparathyroidism, is similar between TET and open thyroidectomy. 3 , 4 However, the BA and TOVA are different TET approaches and have different observation angles. The TOVA can provide excellent surgical exposure for PTC resection and allows direct access to both sides of the central neck with limited tissue dissection.…”
Section: Introductionmentioning
confidence: 99%
“…Since a large case series of transoral endoscopic thyroidectomy was reported in 2016, multiple hospital centers worldwide have introduced this technique and reported their initial experience ( 7 ). Up to now, transoral endoscopic thyroidectomy via vestibular approach (TOETVA) has become one of the most widely used techniques in scarless endoscopic thyroidectomy ( 8 ). Our group has reported a large cohort of TOETVA cases, in which we demonstrated that transoral endoscopic thyroidectomy has the same surgical safety compared with total endoscopic thyroidectomy via areola approach, and conventional open thyroidectomy ( 9 ).…”
Section: Discussionmentioning
confidence: 99%